Studying the impact of informed marketing on the customer experience in Iraqi companies (Al-Mansour Journal, 2025)
The research aimed primarily to determine the role and relationship of enlightened marketing in improving customer experience in Iraqi companies, by conducting interviews with many customers, as well as a number of employees at different administrative levels to explore their opinions about the value of enlightened marketing in customer experience, using descriptive and analytical methods. By preparing a questionnaire and distributing it to the study sample, which consisted of a selected sample of employees and customers of a sample of Iraqi companies. Simple randomization was used to represent the type of research that included 200 participants from these institutions who were selected to complete the questionnaire. After studying the data and hypotheses, the researcher concluded that there is a direct and significant relationship between enlightened marketing and customer experience. The results also showed that the gender variable had a statistically significant impact on the quantitative function of the customer experience. In contrast, no statistically significant differences appeared with regard to the customer experience due to the variables of age, educational level, and income. In addition, it was found that there were significant differences in the sample’s answers regarding the application of enlightened marketing attributed to (customers, employees), with an average of 3.9 and 3.31 for each of them, respectively.
Keywords: customer experience,gender variable,Informed marketing,Age variable,Educational level variable,Income variable.